Academic convocation dedicating the College of Veterinary Medicine, University of Tennessee, September 22, 1979 - University of Tennessee, Knoxville. College of Veterinary Medicine ([1979], 1979)
Highlights of the dedication ceremony.
U-matic.
Keywords: University of Tennessee, Knoxville. -- College of Veterinary Medicine